MOTIVES AND GRATIFICATIONS OF BOGOR STUDENTS IN USING THE INTERNET - Satriani, Imani; Alamsyah, Feri Ferdinan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
Bogor City has 11 tertiary institutions consisting of 2 polytechnics, 3 academies, 3 colleges, and 3 universities. Studentsin Bogor as internet users have certain motives and gratifications to fulfil their needs for informational exchange. Students will decide or not decide to use the internet. In this case, it is certainly influenced by some motives. This qualitative research employs a descriptive survey method. It took place in Bogor Higher Education Institutions which include universities and institutes which provide academic and higher professional education, and academies and polytechnics which only provide the latter. Sampling techniques employed in this research is probability sampling and cluster sampling. Based on the Slovin formula, the determination of a minimum sample by setting precision of 10% (0.1), is 100 people. Then it divides the portions between students from universities and institutes with students from polytechnics and academies about 50% of each. Data collection techniques used in this research include questionnaires, interviews, observation, and literature review. The research results show that there are differences in motives and gratifications between academy students and university students using the internet. The differences are seen in the motives and gratification of information, motives, and gratification of social integration and interaction, motives and gratification of entertainment, as well as motives and gratification of personal identities in using five internet services which include messaging applications, social media, electronic mail, search engines, and video streaming